2003
DOI: 10.1001/jama.289.24.3254
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Long Durations and Different Regimens of Hormone Therapy and Risk of Breast Cancer

Abstract: Context Women using combined estrogen and progestin hormone replacement therapy (CHRT) have an increased risk of breast cancer; however, data on use for long durations and on risk associated with patterns of use are lacking.Objective To evaluate relationships between durations and patterns of CHRT use and risk of breast cancer by histological type and hormone receptor status.Design Population-based case-control study.Setting Three counties in western Washington State.Participants Nine hundred seventy-five wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
184
3
6

Year Published

2004
2004
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(219 citation statements)
references
References 31 publications
26
184
3
6
Order By: Relevance
“…Furthermore, our study demonstrated that most ILCs are characterized by a generally low proliferative index and high ER, PR and AR expression. This steroid receptor pattern clearly suggests a hormonal involvement in the pathogenesis of ILCs [10,23,24,38].…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, our study demonstrated that most ILCs are characterized by a generally low proliferative index and high ER, PR and AR expression. This steroid receptor pattern clearly suggests a hormonal involvement in the pathogenesis of ILCs [10,23,24,38].…”
Section: Discussionmentioning
confidence: 74%
“…The association with HRT use is stronger for lobular carcinoma than for ductal carcinoma [17,18]. In Belgium, Vankrunkelsven et al [7] found a larger decline in invasive lobular than in ductal carcinomas, while inverse results were found in the USA [19].…”
Section: Discussionmentioning
confidence: 98%
“…Ce résultat pourrait sembler encourageant car pendant cette période l'incidence de ce cancer a nettement augmenté passant de 56 pour 100 000 en 1980 à 63 en 1985 et 89 en 2000 [68] soit 58 % après correction pour vieillissement de la population. Il est difficile de distinguer dans cette évolution ce qui revient aux différents facteurs possibles : accroissement du nombre des cas en raison du surdiagnostic (conséquence du dépis-tage), augmentation réelle due à l'exposition aux oestrogènes (puberté plus précoce, âge au premier enfant de 3 ans plus tardif), accroissement de l'indice de masse corporelle, la fréquence des cancers après la ménopause étant influencée par ce facteur [11,45,46,64,75], augmentation de la consommation d'alcool chez les femmes [75] et enfin plus grand usage des traitements hormonaux substitutifs, ce qui augmente la fréquence des cancers du sein [10,22,34,35,56,86] et réduit leur détectabilité par mammographie [28,36,48]. Il est donc devenu nécessaire de mettre en balance les avantages et les inconvénients de ces traitements substitutifs et de limiter leur durée et leurs indications [72].…”
Section: Cancer Du Seinunclassified